Direct Photoalignment and Optical Patterning of Molecular Thin Films. Issue 6 (1st December 2016) - Pithan, Linus; Beyer, Paul; Bogula, Laura; Zykov, Anton; Schäfer, Peter; Rawle, Jonathan; Nicklin, Chris; Opitz, Andreas; Kowarik, Stefan
Abstract : A novel strategy for direct photoalignment of molecular materials using optothermal re‐orientation is introduced. Photoalignment for molecular materials such as the organic semiconductor tetracene is shown, without relying on additional photoreactive dopants or alignment layers. Patterning and polarized light emission, e.g., for polarized organic light emitting diodes is demonstrated.